Odpowiedzi

Najlepsza Odpowiedź!
2009-11-08T13:22:48+01:00

1. 2x+5-3x-12/3=2x+5-3x-4=-x+1
2. 12x+16/4 - 10x+15/5=12x+4-10x+3=2x+7
3. 9-6x/3 - 21 - 14x/7=9-2x-21-2x=-4x-12
4. 4(x - 1)/2 - 3 * 10x - 50/5 =(4x-4)/2-30x-10=2x-2-30x-10=-28x-12
2009-11-08T13:24:16+01:00
1. 2x+5-3x-12/3=-x+1
2. 12x+16/4 - 10x+15/5=2x+7
3. 9-6x/3 - 21 - 14x/7=-12-2x-2x=-4x-12
4. 4(x - 1)/2 - 3 * 10x - 50/5=(4x-4)/2-30x-10=2x-2-30x-10=-28x-12
2009-11-08T13:27:22+01:00
1. 2x+5-3x-4= -x+1
2. 12x+4-10x+3=2x+7
3. -4x-12
4. 4x- 4/2-30x-10= 28x-12